PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR PADA BIDANG JEMBATAN DINAS PUBMTR - Dinny Komala Sari; Marlindawati Marlindawati (Jurnal Ilmiah Matrik, 2023)
Abstract : This research was conducted at the Public Works Department on the bridge midwife. This right was back grounded by the existence of a running system and found several shortcomings that occurred, especially in the archiving of the writing structure in the agenda book and the storage of hardcopy files so that this causes difficulties in conducting searches because they have to open one by one in the recording of the agenda book and there can also be loss or damage to the letter stored in hardcopy form. In accordance with the description and existing problems, the author tried to design an archiving information system using the programming languages Xampp, Phpmyadmin, Sublime text and UML (Use case, Activity and Class Diagram) as the database. As for what resulted from this study, the information system for archiving incoming and outgoing letters in the Bridge Sector at the Public Works Office of Bina Marga and Spatial Planning of South Sumatra Province.